FINANCING DEPOSIT RATIO, BADAN OPERASIONAL PENDAPATAN OPERASIONAL, NON PERFORMING FINANCING DAN PROFITABILITAS PERUSAHAAN PERBANKAN SYARIAH DI INDONESIA - Dodik Hartanto; Siti Nurlaela; Kartika Hendra Titisari (Jurnal Akuntansi dan Keuangan, 2020)
This study aims to determine, test and analyze the FDR, BOPO, NPF and Profitability of sharia banking companies in Indonesia which are registered in the Financial Services Authority (OJK) fourth quarter financial statements of sharia banking companies in the 2016-2018 period. This research is a quantitative research. The  population  in  this  study  is  Islamic  banking  companies  registered  with  the Financial  Services Authority (OJK).  The  sample in this  study  was taken  using  a purposive sampling method that met the sample criteria desired by the researcher. The data used in this study is in the form of documentation. Data analysis techniques used in this study are multiple linear regression analysis and classic assumption test. Based  on  these  results  what  is  done  shows  that  Financing  Deposit  to  Ratio, Operational Costs Operating Income, and Non Performing Financing affect the profitability of Islamic banking companies.